2019
DOI: 10.3390/met9030373
|View full text |Cite
|
Sign up to set email alerts
|

Quenching and Partitioning of Multiphase Aluminum-Added Steels

Abstract: The quenching and partitioning response following intercritical annealing was investigated for three lean TRIP-type high-Al steel compositions. Depending on the intercritical austenite fraction following annealing, the steels assumed either a ferrite/martensite/retained austenite microstructure or a multiphase structure with ferritic, bainitic and martensitic constituents along with retained austenite. The amount of retained austenite was found to correlate with the initial quench temperature and, depending on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…This meant that there were two samples with a size of 5 mm × 10 mm for the XRD measurements and microstructural investigations. The temperature gradient within the experimental samples using the same equipment was investigated in a previous study [37], where it was found that the temperature gradient within the distance 3-6 mm from the thermocouple remains below 3-5 • C at all stages of the heat treatment. The galvanised coating from Steel A was removed and 5 mm × 10 mm sample was prepared for microstructural analysis and XRD measurements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This meant that there were two samples with a size of 5 mm × 10 mm for the XRD measurements and microstructural investigations. The temperature gradient within the experimental samples using the same equipment was investigated in a previous study [37], where it was found that the temperature gradient within the distance 3-6 mm from the thermocouple remains below 3-5 • C at all stages of the heat treatment. The galvanised coating from Steel A was removed and 5 mm × 10 mm sample was prepared for microstructural analysis and XRD measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Table 4 presents M s temperatures of the investigated steels from the dilatometer data, JMatPro ® calculated results for M s temperatures and the austenite carbon contents at IA temperatures. Steel A was studied in dilatometry tests in an earlier study by Nyyssönen et al [37], but the JMatPro ® calculations were repeated for the present study. It was observed that the laboratory experimental steel C had significantly lower M s temperature compared to B and D, which indicates that there were differences in the initial starting microstructures of the steels.…”
Section: Methodsmentioning
confidence: 99%
“…The influence of Si and Al on the mechanical properties has been reported in several studies for conventional transformation induced plasticity (TRIP) [ 12–15 ] to Q&P steels. [ 16–18 ] In general, high Si contents trigger the formation of very strong oxide layers, leading to poor surface characteristics in the case of hot‐rolled steels. Furthermore, after cold rolling these surface oxides result in undesired galvanizing problems.…”
Section: Introductionmentioning
confidence: 99%
“…Third, the steel must be also sufficiently hardenable to reach the initial quenching temperature without allowing for undesired ferritic or bainitic phase transformations during the initial cooling step [20].…”
Section: Influence Of Chemical Composition and Heat Treatment On Mech...mentioning
confidence: 99%
“…In the literature, it is possible to observe a wide range of compositions for the Q&P steel grades. Nyyssönen et al [20] tested three different compositions with a carbon content below 0.2 wt%. The steels were cast and rolled, and they could be hot dip galvanized in an industrial setting using existing technology.…”
Section: Influence Of Chemical Composition and Heat Treatment On Mech...mentioning
confidence: 99%